2010
DOI: 10.1007/s00595-009-4042-5
|View full text |Cite
|
Sign up to set email alerts
|

Thymolipoma. A report of nine cases, with emphasis on its association with myasthenia gravis

Abstract: Thymolipomas are benign tumors that show an excellent outcome. Patients with autoimmune disease symptoms occasionally show an improvement of the symptoms after a resection of the tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
53
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 22 publications
3
53
0
1
Order By: Relevance
“…It usually presents in young age, mean age of 22–26 years, and there is no sex predilection. In some of the series, 40% of patients with thymolipoma had autoimmune diseases like myasthenia gravis,1 5 6 vitamin B 12 deficiency, hypogammaglobulinemia and aplastic anaemia. Those patients with autoimmune disease symptoms may show improvement of their symptoms after resection of the tumour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It usually presents in young age, mean age of 22–26 years, and there is no sex predilection. In some of the series, 40% of patients with thymolipoma had autoimmune diseases like myasthenia gravis,1 5 6 vitamin B 12 deficiency, hypogammaglobulinemia and aplastic anaemia. Those patients with autoimmune disease symptoms may show improvement of their symptoms after resection of the tumour.…”
Section: Discussionmentioning
confidence: 99%
“…Thymolipomas are rare benign thymic neoplasms of anterior mediastinum, constituting fewer than 9% of tumours of the thymus 1 2. They are made up of well-differentiated adipose and thymic tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor in the present patient was a benign tumor consisting of thymic and adipose tissue. The thymic tissue component in thymolipomas, in contrast to thymomas, is separated by large amounts of mature fat with no atypia and no mitotic activity . Ringe et al .…”
Section: Discussionmentioning
confidence: 99%
“…The tumor in the present patient was a benign tumor consisting of thymic and adipose tissue. The thymic tissue component in thymolipomas, in contrast to thymomas, is separated by large amounts of mature fat with no atypia and no mitotic activity (5). Ringe et al reported that half of patients with thymolipoma were asymptomatic, and most cases were coincidentally found to have cardiomegaly on chest X-ray (8).…”
Section: Discussionmentioning
confidence: 99%
“…10 Comparable lesions in the breast, thyroid, thymus, and skin have been classified in the same sense as thymolipoma 47 and adenolipoma. 22,48 In contrast, oncocytic lipoepithelial lesions tend to be predominantly epithelial, thus meriting the designation lipoadenoma to emphasize the predominance of the abnormal oncocytic epithelial component.…”
Section: Discussionmentioning
confidence: 99%